COMPOSITION OF THE CATCHING OF BUBU POLES IN THE VILLAGE OF HALANG ISLAND, KUBU DISTRICT BABUSSALAM ROKAN HILIR DISTRICT RIAU PROVINCE - Daryadi, Rio; Syaifuddin, Syaifuddin; Yani, Alit Hindri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstracKubu Babussalam Sub-district as one of the sub-districts in Rokan Hilir Regency also has potential and focuses its development on the capture fisheries sector. The total production of marine capture fisheries in Rokan Hilir Regency in 2017 amounted to 45,797.79 tons, while the total production of marine capture fisheries in Kubu Babussalam District in 2017 amounted to 8,930.54 tons.The number of fishing gear poles operated in Rokan Hilir Regency in 2015 was 440 units, in 2016 there were 440 units while in 2017 there were 392 units. There was a decrease in the number of pole fishing gear in 2017 which was as many as 120 units (Rokan Hilir District Fisheries Service, 2017). The research was conducted in April – May 2019 in Pulau Halang Village, Rokan Hilir Regency.There was a decrease in the number of pole fishing gear in 2017 which was as many as 120 units (Rokan Hilir District Fisheries Service, 2017). The research was conducted in April – May 2019 in Pulau Halang Village, Rokan Hilir Regency. The purpose of this study was to determine the types of main catch (main catch) and bycatch (bycatch) of pole traps that are operated, the composition of the catches of pole traps that are operated and the number of catches once operating the fishing pole traps are operated. The method used in this study is a direct survey method which includes primary and secondary data.The catches during the study were 14 types of fish including red shrimp (Penaeus monodon), white shrimp (Litopenaeus vannamel), chicken feather fish (Thryssa setirostris), belukang fish (Hexanematucthys sagor), sukain fish (Eleutheonema tetradactylum), gulama fish (Pennahia). argentata), lomek fish (Harpadon nehereus), tongue fish (Cynoglossus lepturus), yellow tail fish (Caesionida), crab (Brachyura), octopus (Octopoda), squid (Mastigoteuthis flammea), stingray (Dasyatis), layur fish (Trichiurus lepturus).Keywords: Composition of Catch, Bubu Pole, Catching Season